Role of emotional disorders, personality features and disorders of intraceptive sensation in development of somatic symptoms at irritable bowel syndrome - Ye. A. Poluektova; A. A. Kurbatova; G. Ye. Rupchev; A. A. Sheptulin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate emotional disorders, personality features and features of intraceptive sensations in patients with irritable bowel syndrome (IBS), as well as the effect of revealed changes on disease severity.Material and methods. Overall 30 patients with confirmed diagnosis of IBS were studied. Number of days of feeling sick for the last year, number of medical encounters for the same time, intensity of abdominal pain according to VAS, frequency of bowel movements per day (number of defecations per day at IBS-D and number of defecations per week at IBS-C) were taken into account in correlation to disease severity and severity of anxiety and depression according to respective scales, to personality features of patients, and also to pattern and volume of individual dictionary for description of internal somatic sensations. Profound investigation including application of questionnaires was carried out for assessment of: dominating personality traits of the patient, his/her emotional features (individual typological questionnaire – ITQ); structure and bulk of individual dictionary for description of internal somatic sensations (test of intraceptive sensation descriptors choice); presence of emotional disorders (respective scales of Hamilton test for anxiety and depression – HARS, HDRS).Results. At analysis of anxiety level with symptoms determining disease severity, moderate positive correlation of total HARS score with severity of disorders of defecation at constipation and number of days with IBS symptoms for the last year (р=0,07) was revealed. At analysis of depression level (total score on HDRS) with symptoms representing severity of disease, statistically significant positive moderate correlation with severity of depressive disorder with degree of disorders of defecation (both for IBS-D, and for IBS-C) and quantity of days with IBS symptoms for the last year was found out (р=0,023; 0,025 and 0,026 respectively). Following correlations between ITQ questionnaire results and symptoms of disease severity were detected as statistical trend: moderate negative correlation between extraversion scale and number of IBS-related medical encounters for the last year (р=0,05), between anxiety scale and degree of disorders of defecation both at IBS-D, and at IBS -C (р=0,05; р=0,06); at the level of statistical significance moderate negative correlation between lability scale and quantity of IBS-related medical encounters (р=0,022) was revealed. At comparison of intensity of symptoms representing severity of disease, in groups of patients formed according to cluster analysis results of the test of intraceptive sensation descriptors choice, it was possible to reveal increase of severity of IBS symptoms from the 3rd to the 1st cluster.Conclusion. Severity of IBS (quantity of medical encounters, total number of days of feeling sick per year, etc.) is determined by severity of anxiety and depressive disorders (by HARS and HDRS scales), disorder of social adaptation (by ITQ test) and distortion of body perception (by test of intraceptive sensation descriptors choice), that it is necessary to take into account at treatment prescription.